1965
DOI: 10.1113/expphysiol.1965.sp001770
|View full text |Cite
|
Sign up to set email alerts
|

On the Sympathetic Innervation of the Parotid Gland of the Cat

Abstract: The postganglionic sympathetic fibres to the parotid gland of cats have been found to go, in most cases, through the middle ear in the tympanic plexus which also contains the preganglionic parasympathetic fibres. The sympathetic fibres do not, however, seem to pass with the postganglionic parasympathetic neurones to the gland in the auriculotemporal nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1966
1966
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Among more recent investigators Richins and Kuntz [1953] found little or no secretion. Some secretion was recorded by Str6mblad [1955], Ohlin and Stromblad [1958], Cragg [1965] and Nordenfelt [1965], but Fritz and Botelho [1969] obtained neither flow of saliva nor secretory potentials when the cervical sympathetic trunk was stimulated. …”
mentioning
confidence: 99%
“…Among more recent investigators Richins and Kuntz [1953] found little or no secretion. Some secretion was recorded by Str6mblad [1955], Ohlin and Stromblad [1958], Cragg [1965] and Nordenfelt [1965], but Fritz and Botelho [1969] obtained neither flow of saliva nor secretory potentials when the cervical sympathetic trunk was stimulated. …”
mentioning
confidence: 99%